Detection of magnetic order in the S=1 chain compound LiVGe2O6 using implanted spin-polarized muons - Blundell, S; Steer, C; Pratt, F; Marshall, I; Hayes, W; Ward, R (2003)
The temperature dependence of the internal field in the one-dimensional S = 1 chain compound LiVGe2O6 has been measured using muon-spin rotation. Two muon-spin-precession frequencies are observed, corresponding to two distinct stopping sites. The results demonstrate that LiVGe2O6 undergoes a second-order phase transition to long-range magnetic order at TN = 24.5 K. In the paramagnetic regime, we find exponential muon-spin relaxation which is dominated by fluctuations of the 51V nuclear moments.